1979
DOI: 10.5271/sjweh.3100
|View full text |Cite
|
Sign up to set email alerts
|

The transmittance and absorption properties of contact lenses

Abstract: The transmittance and absorption properties of contact lenses. Scand. j. work environ. & health 5 (1979) 262-270. The transmittance and absorption properties of certain soft-lens materials with a low and a high water content and a hard-lens material were analyzed by a spectrophotometric technique over a broad spectrum from ultraviolet (195 nm) to far infrared (40,000 nm) radiation. The dry lens materials not only showed marked absorption within the shortwave region of ultraviolet, but also very strong absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The line-shaped distortion in the IR spectrum indicated that spectra (b) and (c) were saturated. This is presumably due to the changes in the thickness of the contact lenses, and the transmittance and absorption are affected by the material [40].…”
Section: Release Of Mps From Contact Lenses To Water 231 Qualitative ...mentioning
confidence: 99%
“…The line-shaped distortion in the IR spectrum indicated that spectra (b) and (c) were saturated. This is presumably due to the changes in the thickness of the contact lenses, and the transmittance and absorption are affected by the material [40].…”
Section: Release Of Mps From Contact Lenses To Water 231 Qualitative ...mentioning
confidence: 99%